2012
DOI: 10.14712/23362936.2015.25
|View full text |Cite
|
Sign up to set email alerts
|

Fröhlich Systems in Cellular Physiology

Abstract: Electromagnetic fields are usually absent in the picture of processes taking place in living cells which is dominated by biochemistry, molecular genetics and microscopic morphology. Yet experimental and theoretical studies suggest that this omission is not justified. At the end of 1960's H. Fröhlich elaborated a semi-phenomenological model of polar oscillating units that are metabolically driven, exchange energy with the cell's internal heat reservoir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Skulachev has suggested that fused mitochondria could act as ‘power cables’ [67]; it is thus interesting that Reynaud has shown that mitochondria can be made to fuse using electric fields in vitro [68]. This would be in keeping with the ideas of Fröhlich about energy transfer involving vibronic coupling, in particular, between mitochondria and microtubules [69]. Certainly, it has been long known that electrics fields affect cell function and shape: calcium has a strong effect on the electrical energy transfer and transistor-like properties of microtubules [70].…”
Section: The Quantum Mitochondrionmentioning
confidence: 91%
“…Skulachev has suggested that fused mitochondria could act as ‘power cables’ [67]; it is thus interesting that Reynaud has shown that mitochondria can be made to fuse using electric fields in vitro [68]. This would be in keeping with the ideas of Fröhlich about energy transfer involving vibronic coupling, in particular, between mitochondria and microtubules [69]. Certainly, it has been long known that electrics fields affect cell function and shape: calcium has a strong effect on the electrical energy transfer and transistor-like properties of microtubules [70].…”
Section: The Quantum Mitochondrionmentioning
confidence: 91%
“…Coherency of resonances has been studied, among others, for microtubules (Sahu et al, 2013 and b). A wave equation describing a Fröhlich system for cellular physiology has been proposed, which describes the coherence between individual oscillations using a number of energy quanta concentrated in one vibrational mode above the thermal equilibrium level and using an ensemble of interactions counting two or three coupled oscillators (Pokorny, 1998;Šrobár, 2012). A model to predict electromagnetic resonances in proteins, RNA and DNA has been proposed, based on findings that energetic periodicities of delocalised electrons along a molecule are critical for the function of proteins, DNA and RNA (Cosic, 2015).…”
Section: Introductionmentioning
confidence: 99%